Status of family planning service delivery for people living with HIV at public hospital settings in Maharashtra: opportunities and challenges - Joshi, Beena N.; Girase, Bhushan A.; Kulkarni, Ragini N.; Begum, Shahina (International Journal Of Community Medicine And Public Health, 2017)
Background: HIV testing and treatment of seropositive pregnant mothers is a much focused and efficiently managed programme as part of convergence plan between National AIDS Control Program and Reproductive and Child Health services under National Health Mission. This paper aims to depict the level of convergence that exists for another most important reproductive health service namely family planning (FP) for PLHIV at public healthcare settings in Maharashtra. Methods: Participatory observations of HIV, FP and STI facilities and key informant interviews of providers at these facilities located in selected secondary (two district hospitals) and tertiary (two teaching hospitals) public hospitals in Maharashtra were conducted as part of larger intervention study. Results: Insufficient health workforce with inadequate knowledge about PLHIV’s eligibility for contraception and discriminated service delivery (25%) was prominent. Only half (50%) key informants were conversant about FP counseling to PLHIV. One-fourth (27%) informants presumed contraceptives as either harmful or contraindicated to PLHIVs. Indenting and supply of FP commodities was extremely inopportune and irregular. More than half of the respondents highlighted many constraints such as no guidelines on convergence, lack of appropriate counseling skills; low staff motivation; inadequate IEC material on dual protection; lack of FP indicators in MIS; over-occupied staff hours; and inadequate M&E for HIV-FP linkages. Conclusions: Despite challenges, sensitizing and training health workforce to eliminate stigma discrimination; reduce delay in service delivery; and improving monitoring of inter-sectoral convergence activities are needed to improve access to reproductive health services for PLHIVs.